Assessment of Rejuvenation Technology and Integrated Plant Nutrient Management in Old Guava Orchard through Farmers’ Participatory Approach - S. K. Pandey; R. P. Singh (Indian Journal of Extension Education, 2013)
An on-farm testing was conducted in old guava orchard on rejuvenation and IPNM technologies aimed to restoring yield and quality production from trees of cv. Allahabad Safeda. Before the implementation of trial, the farmers were unaware about pruning response and role of improved management practices. The eighteen year old trees of selected guava orchard were pruned drastically head back from a height of 2.00 meter in 2007. Topping and hedging of emerging shoots in months of May and October were performed up to year 2009 regularly to develop a good framework as well as better canopy management. Integrated plant nutrient management and other recommended cultural practices were followed in rejuvenated trees and unpruned plants of alternate rows and compared the performance with farmers practice in remaining trees of orchard. It was observed that topping and hedging increased the number of new shoots (below the cut portion) and spread of plant significantly resulting in reduced tree height and improved fruiting potential of trees as compared to farmers practice. The pruning practices resulted in increased flowering shoots (39.66%) and gave higher average yield -1 -1 63.44 kg tree followed by unpruned well managed trees (44.16 kg tree ) with increased yield of 107.72 per cent and 44.59 -1 per cent over farmers practice (30.54 kg tree ). However, the yield in initial year was low in rejuvenated plants (29.00 kg -1 -1 -1 tree ) as compared to T (38.66 kg tree ) and farmers practice (35.50 kg tree ). The economic analysis revealed that B: C 2 ratios were much higher in rejuvenated plants (3.76) than the T (2.38) and farmers practice (1.43). The yield obtained 2 from pruned trees had better quality as compared to farmers practice. The results of experiments provided an eye opening moment to farmers not only to rejuvenate old unproductive orchard, but also interaction effect of pruning response and better management practices of guava trees.